Nano calcium carbonate for biodegradable materials and its preparation method and application

By using the combination of modified nano calcium carbonate masterbatches and other components, a reinforced toughening material suitable for degrading plastics is prepared, which solves the problem of insufficient ductility and toughness of degraded plastics in the prior art, and achieves significant performance improvement and degradation rate promotion of the material.

CN116023771BActive Publication Date: 2025-03-07GUANGXI PINGGUO RUNFENG CALCIUM NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310113083.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-03-07
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the ductility and toughness of materials in the field of degraded plastics, especially the addition of nano-grade calcium carbonate to brittle substrates, and it is difficult to significantly improve these properties.

Method used

Nano calcium carbonate masterbatches made of modified nano calcium carbonate, nitrogen-containing inorganic salts, tributyl acetyl citrate, cellulose acylate and polybutylene glycol oxylate are prepared through specific process flows such as heating, stirring and extrusion granulation to prepare reinforced toughening materials suitable for degrading plastics.

Benefits of technology

Without losing strength and modulus, the ductility and toughness of degraded plastics are significantly improved, and the degradation rate of degraded materials is promoted. The process is simple and suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano calcium carbonate special for biodegradable materials, a preparation method and an application thereof. The nano calcium carbonate of the invention is prepared from the following raw materials in percentage by mass: 65-75% of modified nano calcium carbonate powder; 3-8% of nitrogen-containing inorganic salt; 3-8% of acetylcitrate tributyl; 1-2% of cellulose acylate; 5-10% of polybutylene glycol oxalate; and 10-15% of PLA resin. The nano calcium carbonate prepared by the invention has good compatibility with degradable plastic substrates, can effectively improve the ductility and toughness of degradable plastics without losing strength and modulus, and can promote the degradation rate of degradable materials, and each component can synergistically enhance the effect, the preparation process is simple, and it is suitable for industrial promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to nano calcium carbonate material technology, and specifically relates to a nano calcium carbonate special for biodegradable material and a preparation method and application thereof. Background Art

[0002] As people's environmental awareness increases, biodegradable materials have attracted more and more attention worldwide. Polylactic acid (PLA) is regarded as one of the most popular commercial biodegradable materials because it is biodegradable, compostable, non-toxic and harmless to humans and the environment. However, some poor physical properties of PLA, such as poor toughness, dimensional instability, low melt viscosity and slow crystallization rate, limit its processing and application. Conventional technical means, such as adding nucleating agents, mixing with fiber or powder particles, chain extension and cross-linking, can improve certain properties to a certain extent.

[0003] Calcium carbonate is a commonly used modified filler for biodegradable plastics such as PLA because of its low price, non-toxicity and environmental protection. It can effectively improve the thermal stability and dimensional stability of polymers and reduce processing costs. However, in brittle substrates such as PLA, it is difficult to improve its ductility and toughness even if nano-scale calcium carbonate is filled.

[0004] CN114685954A discloses a degradable masterbatch for tableware and a preparation method thereof, wherein the degradable masterbatch is prepared from the following raw materials in parts by weight: 15-25 parts of PLA, 25-35 parts of PBS, 75-85 parts of natural fillers, 0.5-1 parts of wetting agents, and 4-6 parts of other reagents. Leaf fibers and wood fibers are fibrous fillers, which have no toughening effect in the system and can only play a reinforcing effect.

[0005] CN113072786A discloses a nano calcium carbonate masterbatch and its preparation method and application in UPVC reinforcement and toughening. The nano calcium carbonate masterbatch of the invention is made of coated modified nano calcium carbonate, PVC resin, calcium-zinc composite stabilizer, polyurethane prepolymer, polytetrahydrofuran polyol, lubricant and ethylene-vinyl acetate copolymer elastomer. However, the nano calcium carbonate masterbatch of the invention is limited to the field of PVC and is not applicable to the field of degradable plastics.

[0006] CN114181463A discloses an ultrafine nano calcium carbonate masterbatch, pearlescent film and preparation method thereof, wherein the masterbatch is mainly made of first and second homopolymerized polypropylenes, first and second dispersing aids, first and second lubricants, antioxidants and the remainder of modified nano calcium carbonate, wherein the modified nano calcium carbonate is formed by surface modification of nano calcium carbonate with ethylene glycol. The nano calcium carbonate masterbatch prepared by this technology uses polypropylene as a carrier, which is also not suitable for the field of degradable plastics. Therefore, in the field of degradable plastics, it is urgently necessary to develop a nano calcium carbonate masterbatch technology suitable for strengthening and toughening brittle materials. Summary of the invention

[0007] The purpose of the present invention is to overcome at least one shortcoming of the prior art and to provide a nano calcium carbonate special for biodegradable materials and a preparation method and application thereof.

[0008] The technical solution adopted by the present invention is:

[0009] In a first aspect, the present invention provides a nano-calcium carbonate specially used for biodegradable materials, characterized in that it is prepared from the following raw materials in percentage by weight: 65-75% modified nano-calcium carbonate powder; 3-8% nitrogen-containing inorganic salt; 3-8% acetyl tributyl citrate; 1-2% cellulose acylate; 5-10% polybutylene glycol oxalate; and 10-15% PLA resin; the modified nano-calcium carbonate powder is obtained by modifying a nano-calcium carbonate suspension with saturated fatty acids and polycaprolactone polyethylene glycol carboxyl derivatives.

[0010] In some examples, the preparation method of the modified nano calcium carbonate powder is:

[0011] 1) heating a nano calcium carbonate suspension, and then adding a saturated fatty acid and a polycaprolactone polyethylene glycol carboxyl derivative to perform an activation modification reaction to obtain a modified nano calcium carbonate suspension;

[0012] 2) The modified nano calcium carbonate suspension is sequentially dehydrated, dried, crushed and classified to obtain modified nano calcium carbonate powder.

[0013] In some embodiments, the specific surface area of ​​the nano calcium carbonate is 26 to 40 m 2 / g, and the mass concentration in the suspension is 10% to 13%.

[0014] In some examples, the saturated fatty acid is selected from at least one of saturated fatty acids with 12 to 18 carbon atoms.

[0015] In some examples, the amount of the saturated fatty acid is 1-2% of the mass of the nano-calcium carbonate, and the amount of the polycaprolactone polyethylene glycol carboxyl derivative is 3.0-5.0% of the mass of the nano-calcium carbonate.

[0016] In some examples, the activation modification reaction temperature is 70-90° C., and the reaction time is 60-120 min.

[0017] In some examples, the nitrogen-containing inorganic salt is selected from at least one of calcium nitrate, urea, and ammonium carbonate, and / or the cellulose acylate is selected from at least one of cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate.

[0018] In some examples, the method for preparing nano calcium carbonate comprises the following steps:

[0019] 1) The modified nano-calcium carbonate powder, the nitrogen-containing inorganic salt and the cellulose acylate are stirred and mixed and heated uniformly, and then acetyl tributyl citrate is added when the temperature reaches 68-72° C., polybutylene oxalate and PLA resin are added when the temperature reaches 88-92° C., and the premix is ​​obtained by discharging the material at 100-110° C.;

[0020] 2) After the premix is ​​left to stand for 24 to 48 hours, it is extruded and granulated at a temperature of 160 to 190° C. to obtain the nano calcium carbonate masterbatch specially used for biodegradable materials.

[0021] In a second aspect, the invention provides an application of nano calcium carbonate in the preparation of enhanced and toughened degradable plastics.

[0022] In a third aspect, the present invention provides a biodegradable plastic, to which the nano calcium carbonate is added.

[0023] The beneficial effects of the present invention are as follows: the nano calcium carbonate plastic masterbatch prepared by the present invention has good compatibility with degradable plastic substrates such as PLA and PBAT, can effectively improve the ductility and toughness of degradable plastics without losing strength and modulus, and can promote the degradation rate of degradable materials. Moreover, the preparation process is simple and suitable for industrial promotion and application. DETAILED DESCRIPTION

[0024] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention. Example

[0025] A method for preparing nano calcium carbonate masterbatch for biodegradable materials comprises the following steps:

[0026] 1) Take the specific surface area of ​​26 m 2 / g of nano calcium carbonate suspension (mass concentration of 13%) was heated to 90°C and then 1.0% (calculated on dry basis of calcium carbonate, the same below) of stearic acid and 3.0% of polycaprolactone polyethylene glycol carboxyl derivative (PCL3000-PEG800-COOH) were added for activation modification for 60 minutes;

[0027] 2) Dehydrating, drying, crushing and classifying the modified nano calcium carbonate suspension in sequence to obtain modified nano calcium carbonate powder;

[0028] 3) Add 75% nano calcium carbonate, 3% calcium nitrate and 1% cellulose acylate under low-speed stirring. After starting high-speed stirring, raise the temperature to about 70°C and add 3% acetyl tributyl citrate. When the temperature reaches 90°C, add 8% polybutylene oxalate and 10% PLA resin. Discharge at 110°C.

[0029] 4) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder, and the temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano calcium carbonate plastic masterbatch for reinforcing and toughening the degradable plastic. Example

[0030] A method for preparing biodegradable nano calcium carbonate masterbatch comprises the following steps:

[0031] 1) Take the specific surface area of ​​40m 2 / g of nano calcium carbonate suspension (mass concentration of 10%) was heated to 90°C and then added with 2.0% (calculated on dry basis of calcium carbonate, the same below) of lauric acid and 5.0% of polycaprolactone polyethylene glycol carboxyl derivative (PCL2000-PEG1000-COOH) for activation modification for 120 min;

[0032] 2) Dehydrating, drying, crushing and classifying the modified nano calcium carbonate suspension in sequence to obtain modified nano calcium carbonate powder;

[0033] 3) Add 70% nano calcium carbonate, 5% calcium nitrate and 1% cellulose acylate under low-speed stirring. After starting high-speed stirring, raise the temperature to about 70°C and add 6% acetyl tributyl citrate. When the temperature reaches 90°C, add 6% polybutylene oxalate and 12% PLA resin. Discharge at 110°C.

[0034] 4) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder, and the temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano calcium carbonate plastic masterbatch for reinforcing and toughening the degradable plastic. Example

[0035] A method for preparing biodegradable nano calcium carbonate masterbatch comprises the following steps:

[0036] 1) Take the specific surface area of ​​35m 2 / g of nano calcium carbonate suspension (mass concentration of 10%) was heated to 70°C and then 1.5% (calculated on dry basis of calcium carbonate, the same below) of palmitic acid and 4.5% of polycaprolactone polyethylene glycol carboxyl derivative (PCL5000-PEG1000-COOH) were added for activation modification for 100 min;

[0037] 2) Dehydrating, drying, crushing and classifying the modified nano calcium carbonate suspension in sequence to obtain modified nano calcium carbonate powder;

[0038] 3) Add 65% nano calcium carbonate, 8% calcium nitrate and 2% cellulose acylate under low-speed stirring. After starting high-speed stirring, raise the temperature to about 70°C and add 8% acetyl tributyl citrate. When the temperature reaches 90°C, add 7% polybutylene oxalate and 10% PLA resin. The material can be discharged at 110°C.

[0039] 4) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder, and the temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano calcium carbonate plastic masterbatch for reinforcing and toughening the degradable plastic. Example

[0040] 1) Take the specific surface area of ​​30m 2 / g of nano calcium carbonate suspension (mass concentration of 10%) was heated to 70°C and then 1.5% (calculated on dry basis of calcium carbonate, the same below) of stearic acid and 4.0% of polycaprolactone polyethylene glycol carboxyl derivative (PCL5000-PEG1000-COOH) were added for activation modification for 100 min;

[0041] 2) Dehydrating, drying, crushing and classifying the modified nano calcium carbonate suspension in sequence to obtain modified nano calcium carbonate powder;

[0042] 3) Add 65% nano calcium carbonate, 3% calcium nitrate and 1% cellulose acylate under low-speed stirring. After starting high-speed stirring, raise the temperature to about 70°C and add 6% acetyl tributyl citrate. When the temperature reaches 90°C, add 10% polybutylene oxalate and 15% PLA resin. The material can be discharged at 110°C.

[0043] 4) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder, and the temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano calcium carbonate plastic masterbatch for reinforcing and toughening the degradable plastic.

[0044] 1) Add commercially available ordinary nano calcium carbonate (specific surface area 30.23m 2 / g, modified with 5.5% stearic acid) 65%, 3% calcium nitrate and 1% cellulose acylate. After high-speed stirring is started, the temperature is raised to about 70°C and 6% acetyl tributyl citrate is added. When the temperature reaches 90°C, 10% polybutylene oxalate and 15% PLA resin are added. The material can be discharged at 110°C.

[0045] 2) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder. The temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano-calcium carbonate plastic masterbatch for the biodegradable plastic of this comparative example.

[0046] 1) Add 65% of the nano calcium carbonate prepared in Example 4 under low-speed stirring, start high-speed stirring, raise the temperature to about 70°C, add 5% of citrate, add 10% of PBAT resin and 20% of PLA resin after the temperature reaches 90°C, and discharge at 110°C.

[0047] 2) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder. The temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano-calcium carbonate plastic masterbatch for the biodegradable plastic of this comparative example.

[0048] The cellulose acylate is subtracted from Example 4, and the remaining proportion is evenly distributed on the polybutylene oxalate resin and the PLA resin according to the proportion of Example 4:

[0049] 1) Add 65% of the nano calcium carbonate and 3% of calcium nitrate prepared in Example 4 under low-speed stirring, and after starting high-speed stirring, raise the temperature to about 70°C and add 6% of citrate. After the temperature reaches 90°C, add 10.4% of polybutylene oxalate resin and 15.6% of PLA resin, and discharge at 110°C.

[0050] 2) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder. The temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano-calcium carbonate plastic masterbatch for the biodegradable plastic of this comparative example.

[0051] Calcium nitrate was subtracted from Example 4, and the remaining proportion was evenly distributed on the polybutylene oxalate resin and the PLA resin according to the proportion of Example 4:

[0052] 1) Add 65% of the nano calcium carbonate prepared in Example 4 and 1% of cellulose acylate under low-speed stirring, start high-speed stirring, heat to about 70°C, add 6% of citrate, add 11.2% of polybutylene oxalate resin and 16.8% of PLA resin after the temperature reaches 90°C, and discharge at 110°C.

[0053] 2) After the mixture is allowed to stand for 24 hours, it is extruded into granules through a twin-screw extruder. The temperature settings of each section of the extruder are 160°C-165°C-170°C-175°C-180°C-185°C-185°C-190°C-185°C-180°C (die temperature) in sequence, to obtain the nano-calcium carbonate plastic masterbatch for the biodegradable plastic of this comparative example.

[0054] The above examples and comparative examples were subjected to blown film processing according to a formula of 100 parts of PLA resin + 15 parts of nano-calcium carbonate (based on the actual solid content of calcium carbonate, taking Example 4 as an example, 23 parts of nano-calcium carbonate masterbatch need to be actually added). The film was tested for mechanical properties according to GB / T 1040.3-2006, and the biodegradability (180d) was tested according to GB / T 19277.1-2011. The results are shown in Table 1.

[0055] Table 1

[0056] Experimental recipe Longitudinal tensile strength, Mpa Longitudinal elongation at break, % Transverse tensile strength, Mpa Transverse elongation at break, % Biodegradability (180d), % Example 1 7.22 398 5.18 314 87.4 Example 2 7.07 402 5.29 376 88.1 Example 3 7.19 413 5.03 348 92.3 Example 4 7.46 430 5.15 362 89.7 Comparative Example 1 6.18 236 4.05 175 79.3 Comparative Example 2 5.11 113 3.12 74 68.6 Comparative Example 3 5.42 342 3.39 281 83.1 Comparative Example 4 6.94 380 5.96 319 72.6

[0057] As can be seen from the above table, the nano calcium carbonate plastic masterbatch prepared in Examples 1 to 4 has a significant strengthening and toughening effect on degradable plastics, which is better than Comparative Examples 1 and 2 prepared using commercially available ordinary nano calcium carbonate and traditional formulas. Although Comparative Example 3 obtains a better elongation at break, the strength is low, which is a typical plasticizer precipitation phenomenon. In Comparative Example 4, the mechanical properties in all aspects are similar to those in the embodiment, but the biodegradability rate is low. It shows that the various components of the nano calcium carbonate masterbatch of the present invention can synergistically enhance the ductility and toughness of degradable plastics, and can promote the degradation rate of degradable materials.

[0058] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A nano calcium carbonate masterbatch for biodegradable materials, characterized in that: The nano calcium carbonate masterbatch is prepared from the following raw materials in percentage by weight: 65-75% modified nano calcium carbonate powder; 3-8% nitrogen-containing inorganic salt; 3-8% acetyl tributyl citrate; 1-2% cellulose acylate; 5-10% polybutylene glycol oxalate; 10-15% PLA resin; Wherein, the nitrogen-containing inorganic salt is selected from at least one of calcium nitrate, urea, and ammonium carbonate; The cellulose acylate is selected from at least one of cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate; Wherein, the preparation method of the modified nano calcium carbonate powder is: The nano-calcium carbonate suspension is heated, and then 1-2% of the mass of the nano-calcium carbonate is added with a saturated fatty acid and 3.0-5.0% of the mass of the nano-calcium carbonate is added with a polycaprolactone polyethylene glycol carboxyl derivative to carry out an activation modification reaction at 70-90° C. for 60-120 minutes to obtain a modified nano-calcium carbonate suspension, wherein the saturated fatty acid is selected from at least one of saturated fatty acids with 12 to 18 carbon atoms; The modified nano calcium carbonate suspension is sequentially dehydrated, dried, crushed and classified to obtain modified nano calcium carbonate powder.

2. The nano calcium carbonate masterbatch according to claim 1, characterized in that The specific surface area of ​​the nano calcium carbonate is 26 to 40 m 2 / g, and the mass concentration in the suspension is 10% to 13%.

3. The method for preparing the nano calcium carbonate masterbatch according to claim 1 or 2, characterized in that: The following steps are involved: The modified nano-calcium carbonate powder, the nitrogen-containing inorganic salt and the cellulose acylate are stirred and mixed uniformly and heated, and then acetyl tributyl citrate is added when the temperature reaches 68-72°C, and polybutylene oxalate and PLA resin are added when the temperature reaches 88-92°C, and the premix is ​​obtained by discharging the material at 100-110°C; After the premix is ​​left to stand for 24 to 48 hours, it is extruded and granulated at a temperature of 160 to 190° C. to obtain the nano calcium carbonate masterbatch specially used for biodegradable materials.

4. Use of the nano calcium carbonate masterbatch according to claim 1 or 2 in the preparation of a reinforcing and toughening agent for degradable plastics.

5. A biodegradable plastic, characterized in that: The nano calcium carbonate masterbatch according to claim 1 is added therein.

Citation Information

Patent Citations

  • Superfine nano calcium carbonate master batch, pearlized film and preparation method of pearlized film

    CN114181463A

  • Preparation method of special nano-calcium carbonate for plastic

    CN107555461A

  • Nano calcium carbonate master batch as well as preparation method and application thereof in reinforcing and toughening of UPVC (Unplasticized Polyvinyl Chloride)

    CN113072786A

  • Near-infrared two-region bifluorescence emission rare earth nano probe as well as preparation method and application thereof

    CN115505388A

  • Special nano calcium carbonate material for PLA transparent degradable master batch and modification method

    CN115537041A